Dukungan Tokoh Masyarakat dalam Keberlangsungan Desa Siaga di Desa Kenongo Kecamatan Gucialit Kabupaten Lumajang (Community Leaders’ Support in the Sustainability of Alert Village in Kenongo Village, Sub District of Gucialit, Lumajang Regency) - Muhammad Abdillah Akbar; Husni Abdul Gani; Erdi Istiaji (Pustaka Kesehatan, 2015)
Government sets up Alert Village program that has a component of basic health service,community empowerment through development of Community-Sourced Health Efforts. One ofActive Alert Villages in Indonesiat is Kenongo Village, District of Gucialit, Lumajang Regency.Thesuccess of the formation of Alert Village in Kenongo Village. The purpose of research to knowthe form of support from community Leders’ in an emotional manner , the award , instrumental ,in the sustainability and informative of alert village in Kenongo village.This research is adescriptive research with qualitative approach. Determination of informants in this research usedpurposive technique. Data were collected by indepth interview, triangulation, unstructuredobservation and documentation. The provision of social support from community leaders wasdivided into four, emotional support was given by giving attention and motivation to thecommunity members, so that they community were moved to participate in the activities. Theappreciative support by community leaders was given by giving appreciation and attention topeople who participate in activities of Active Alert Village. Other appreciation was given by givingrewards to the community in the form of development assistance of health facilities. The form ofinstrumental support by community leaders by providing aids needed by the community.Informative support given by community leaders by providing information through gatheringvillage officers and cadres..Keywords: Community leaders’ support, alert Village, heatlh promotion